Lack of small colony variants of Staphylococcus aureus from lower respiratory tract specimens. Issue 5 (22nd March 2017) - Carzino, Rosemary; Hart, Emily; Sutton, Philip; King, Louise; Ranganathan, Sarath; ,
Abstract: Background: Small‐colony variants (SCVs) of Staphylococcus aureus are associated with worse lung disease in children with Cystic Fibrosis (CF), exhibit a higher resistance to antibiotics and co‐colonize more commonly with Pseudomonas aeruginosa compared to the normal phenotype. The prevalence of SCVs in lower airway specimens from children with CF is largely unknown. Methods: Each visible morphotype of S. aureus was subcultured onto horse blood agar (HBA) to enable identification of SCVs. Results: Sixty‐one samples from 41 children (mean age 11.7 (SD 5.3) years) were identified with a positive S. aureus culture from lower respiratory tract specimens collected in 2014‐2015. None of the differing morphotypes isolated were identified as S. aureus SCVs. Conclusion: In a center where anti staphylococcal prophylaxis is adopted, S. aureus SCVs were not isolated from the lower airways specimens in young children with CF indicating that acquisition of small colony variant S. aureus may not be a significant clinical problem in young children with CF.